Exercise Barriers and Adherence to Recommendations in Patients With Cancer. Issue 7 (July 2021) - Ng, Amy H.; Ngo-Huang, An; Vidal, Marieberta; Reyes-Garcia, Ariadne; Liu, Diane D.; Williams, Janet L.; Fu, Jack B.; Yadav, Rajesh; Bruera, Eduardo
Abstract : PURPOSE: The American College of Sports Medicine exercise guidelines for cancer survivors encourage a combination of 150 minutes of moderate-intensity aerobic activity and 2-3 weekly sessions of strength training. Cancer survivors often experience more barriers to meeting recommended guidelines because of side effects from cancer treatments. Our aim was to measure the cancer survivors' adherence and barriers with these recommendations. METHODS: Two hundred adult cancer survivors completed surveys (Stanford Patient Education Research Center Exercise Behaviors Survey and an exercise barrier scale) reporting their physical activity, barriers to physical activity, and symptom assessment. RESULTS: A total of 68/200 participants (34%) reported adhering to the recommended physical activity guidelines of 150 minutes or more per week. Those who adhered to the guidelines reported fewer barriers to exercise (mean of 2.44 compared with 4.15 barriers, P < .0001). Female participants ( P = .01), higher number of barriers, and feeling of poor well-being were less likely to report at least 60 or 150 minutes of exercise time. Lack of interest ( P = .003) and self-discipline ( P = .001) were reported as barriers. These participants were more likely to report high symptom burden of pain ( P = .007) and fatigue ( P = .005). Participants who reported < 60 minutes of exercise reported lack of enjoyment ( P = .03), lack of equipment ( P = .01), and symptoms of poor appetite, poor well-being, and increased dyspnea. CONCLUSION: Although recommendations are given for exercise, adherence to recommendations is low. Issues of motivation, including lack of interest and self-discipline, and symptoms of pain and fatigue were some of the main reported barriers to adhering to the recommended exercise guidelines. Therefore, interventions aimed at increasing motivation and treating symptoms could improve cancer survivor adherence to recommended exercise guidelines.